Secondary nucleation and elongation occur at different sites on Alzheimer’s amyloid-β aggregates - Scheidt, Tom (Sci Adv, 2019)
The aggregates of the Aβ peptide associated with Alzheimer’s disease are able to both grow in size as well as generate, through secondary nucleation, new small oligomeric species, that are major cytotoxins associated with neuronal death. Despite the importance of these amyloid fibril-dependent processes, their structural and molecular underpinnings have remained challenging to elucidate. Here, we consider two molecular chaperones: the Brichos domain, which suppresses specifically secondary nucleation processes, and clusterin which our results show is capable of inhibiting, specifically, the elongation of Aβ fibrils at remarkably low substoichiometric ratios. Microfluidic diffusional sizing measurements demonstrate that this inhibition originates from interactions of clusterin with fibril ends with high affinity. Kinetic experiments in the presence of both molecular chaperones reveal that their inhibitory effects are additive and noncooperative, thereby indicating that the reactive sites associated with the formation of new aggregates and the growth of existing aggregates are distinct.